1971
DOI: 10.1161/01.cir.43.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Human Tricuspid Valve

Abstract: The morphology of 50 normal tricuspid valves was studied. The surface of the leaflets was divided into three zones: (1) the rough zone, into which most of the chordae tendineae are inserted, (2) the basal zone, and (3) the clear zone, which lies between the rough and basal zones.Five types of chordae were distinguished by their morphology and mode of insertion: fan-shaped, rough zone, basal, free edge, and deep chordae. The last two types are unique to the tricuspid valve.If fan-shaped chordae, used to define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
143
4
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(166 citation statements)
references
References 6 publications
14
143
4
5
Order By: Relevance
“…In contrast to the anterior leaflet, the septal leaflet experienced little change in RLL as an effect of dilatation. This may be explained by previous studies that have reported the large number of chordae insertions to the septal leaflet from the septum 24 and the possibility for restricted motion. Although it is accepted that annular dilatation may result in TR, it is not the only mechanism.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In contrast to the anterior leaflet, the septal leaflet experienced little change in RLL as an effect of dilatation. This may be explained by previous studies that have reported the large number of chordae insertions to the septal leaflet from the septum 24 and the possibility for restricted motion. Although it is accepted that annular dilatation may result in TR, it is not the only mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…We believe that this is because the anterior leaflet attempts to compensate for the increase in the orifice area created by dilatation of the annulus by reaching to cover it. Multiple studies have reported the anterior leaflet to be the longest and largest in area compared with the posterior and septal leaflets, 24,26 which may be the body's attempt to compensate for annular dilatation up to a certain level. In contrast to the anterior leaflet, the septal leaflet experienced little change in RLL as an effect of dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first diagnostic criteria for Ebstein's anomaly using a multi-crystal two-dimensional system was defined by Hagan in 1974 [33] and they were able to recognize the apical displacement of the septal tricuspid leaflet and an elongated anterior tricuspid leaflet with increased excursion. The septal leaflet of the tricuspid valve attaches chiefly to the ventricular septum, but part of its basal attachment is to the posterior wall of the right ventricle [34] and it normally exhibits a slight but distinct apical displacement of its basal attachment to the central fibrous body compared to the mitral valve. The distal displacement of septal origin of tricuspid valve seems to be the best echocardiographic criterion as the characteristic sign for Ebstein's anomaly and the degree of maximal displacement in normal hearts varies considerably with a mean difference of approximately 6 mm with mitral valve.…”
Section: Echocardiographic Featuresmentioning
confidence: 99%